The dialectical constitution of significations and the formation of scientific concepts about synanthropic animals - Fernandes, Guilherme Augusto [UNESP]; Campos, Luciana Maria Lunardi [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2021)
This article was based on a master's thesis research that had as a central question “which propositions for pedagogical practice, in the teaching of Science and Biology, could be elaborated from historical-critical pedagogy, considering the significations of students about synanthropic animals?” and as objective analyzing the significations of third year high school's students about synanthropic animals and extracting pedagogical appointments for the Science and Biology Teachings. This text develops some dissertation's analyzes about the role of the school as a means of socializing scientific concepts for a human formation based on social practice. Participants formed dialogue groups about animals of public health relevance. The analysis followed the methodology of nuclei of significations. As results, we found nuclei about emotions and reactions to animals; descriptions of biological characteristics; and the non-scientific cultural symbolic universe. From these analyzes, pedagogical notes were extracted based on the historical-critical pedagogy.
A constituição dialética das significações e a formação de conceitos científicos sobre animais sinantrópicos
Keywords: Biology teaching; Historical-critical pedagogy; Historical-cultural psychology; Science teaching